New outbreaks of Aujeszky's disease in the State of Minas Gerais. IV. The transmission of the Aujeszky's virus by placentary route in the spontaneous disease of a bovine - Silva, Renato Augusto da; Gióvine, Nestor (Pesquisa Agropecuaria Brasileira, 2024)
In a natural outbreak of Aujeszky's disease in the Município of Jequitinhonha, State of Minas Gerais, the authors isolated the Aujeszky's virus from separated suspensions of spleen, liver and brain of a nine months old bovine foetus which they removed from the uterus of a cow destroyed for diagnostic purpose. The cow had shown symptoms of the disease for eight days. The virus was isolated from its spinal cord and blood.